THE EFFECT OF RISK AND RETURN ON STUDENTS' INTEREST IN INVESTING IN MUTUAL FUNDS WITH INVESTMENT KNOWLEDGE AS MODERATION VARIABLES (Study on Students of the Faculty of Economics and Islamic Business UIN Raden Intan Lampung) - Wulandari, Putri Nanda (REVENUE: Jurnal Manajemen Bisnis Islam, 2023)
Based on KSEI data, capital market investors continue to show improvement in recent years. Until February 2022, the number of capital market investors is dominated by the younger generation, but based on observations from pre-research data from researchers at UIN Raden Intan Lampung Students regarding Mutual Fund Investment, it turns out that they are still ordinary and some are even reluctant to invest in mutual funds, which shows that their investment interest is still low. The formulation of the problem in this study is whether risk and return have a partial effect on student interest in investing in mutual funds, whether investment knowledge moderates the relationship between risk to student interest in investing in mutual funds, does investment knowledge moderate the relationship between return on student interest in investing in mutual funds and how student interest in investing in mutual funds in an Islamic economic perspective. This study used a quantitative approach. This research was conducted on students who are or have taken the Financial Management course at the Faculty of Economics and Islamic Business UIN Raden Intan Lampung, the sample in this study was 96 respondents. Sampling is done by purposive sampling. The data analysis method uses SEM (Structural equation modeling) using Partial Least Square (PLS) and data management is carried out using SmartPLS 3 software. The results of this study show that the variables Risk and Return partially have a positive and significant effect on Student Interest in Investing in Mutual Funds. The R2 test shows that the R2 value of Investment Interest is 0.546 which means that the value shows that Risk and Return contribute 54.6% and the remaining 46.4% to other variables. Then for variable moderation, investment knowledge weakens the relationship between risk and investment interest significantly, this shows that investment knowledge weakens the relationship between risk and student interest in investing in mutual funds, meaning that investment knowledge moderates the relationship between risk and student interest in investing in mutual funds. Furthermore, investment knowledge strengthens the relationship between return and investment interest insignificantly, this shows that investment knowledge strengthens the relationship between return and student interest in investing in mutual funds but the effect is not large, meaning that investment knowledge does not moderate the relationship between return and student interest in investing in mutual funds.